ETHANO BOTANICAL PROPERTIES OF UNEXPLORED PLANT KHANDU CHAKKA (EHRETIA LAEVIS ROXB.) - Rushikesh, *Thakre; Shyam, Bhutada; Bharat, Chouragade; Pramod, Khobragde; Ketaki Ravindra, Harne (International Journal of Ayurveda and Pharma Research, 2016)
In India many Folklore plants are used traditionally for medicinal purposes. The present review summarizes the comprehensive information concerning the Ethano Botanical properties, Ayurvedic properties and Phytochemistry of Ehretia laevis. All references about this plant reviewed, along with local survey. Predominant chemicals from this plant are Naphthoquinone derivative named lewisone, n-octatricontane, baurenol acetate, baurenol, ursolic acid, Amino acids, Proteins, Lipids, Minerals like Ca,Na, NH3, Mg, Fe, Mn, K, P, Zn, Cu and Si, Total phenolics (97.21mg gallic acid equivalent (GAE)/g) content in leaves, Tannins (64.12mg tannic acid equivalent (TAE)/g) in stem bark, flavonoids (57.23mg rutin equivalent (RE)/g) and Vitamin C (56.09mg ascorbic acid equivalent (AAE)/g) in fruits, leaves and fruits showed the presence of acontanes, decanoic acids, phthalic acid, phytol, Î± and Î² amyrin, piperazine, phenylephrine. Benzoquinones:- 1,4naphthoquinone lewisone, Bauerenol, Bauerenol acetate, Î±-amyrin, Betulin, Lupeol, Betulinic acid, Î²-sitosterol. Dodecane, Tridecene, Tetradecane, n Octylcyclohexane, Tridecanol, Hexadecane, Decyl cyclohexane, Heptadecane, Nonadecane, Tetratetracontane, Di â€“ n octyl phthalate. Amino acid- Butyric acid, Ornithine, Cysteine, Histidine, Arginine, Serine, Hydroxy proline, Glutamic acid, Proline, Lysine, Tryptamine having various therapeutic properties. In Ayurveda this plant is used for Prameha (Diabetics) and Vishaghna (Anti-venom). Leaves contain Di â€“ n octyl phthalate chemical which has properties of anti venom while Amino acid â€“Cysteine, has anti diabetic properties. In Wardha district of Maharashtra India, Ehretia laevis plant is mainly used for wound healing, joint pain and minor fractures by local peoples with promising results and this plant commonly known as Khandu Chakka.